Phloem-Triggered Virus-Induced Gene Silencing Using a Recombinant Polerovirus - Bortolamiol-Bécet, Diane; Monsion, Baptiste; Chapuis, Sophie; Hleibieh, Kamal; Scheidecker, Danièle; Alioua, Abdelmalek; Bogaert, Florent; Revers, Frédéric; Brault, Véronique; Ziegler-Graff, Véronique (Frontiers in Microbiology, 2018)
The phloem-limited poleroviruses infect Arabidopsis thaliana without causing noticeable disease symptoms. In order to facilitate visual infection identification, we developed virus-induced gene silencing (VIGS) vectors derived from Turnip yellows virus (TuYV). Short sequences from the host gene AtCHLI1 required for chlorophyll biosynthesis (42 nucleotides in sense or antisense orientation or as an inverted-repeat (IR), or an 81 nucleotide sense fragment) were inserted into the 3’ non-coding region of the TuYV genome to screen for the most efficient and robust silencing vector. All recombinant viruses produced a clear vein chlorosis phenotype on infected Arabidopsis plants due to the expression inhibition of the AtCHLI1 gene. The introduction of a sense-oriented sequence into TuYV genome resulted in a virus exhibiting a more sustainable chlorosis than the virus containing an IR of the same length. This observation was correlated with a higher stability of the sense sequence insertion in the viral genome. In order to evaluate the impact of the TuYV silencing suppressor P0 in the VIGS mechanism a P0 knock-out mutation was introduced into the recombinant TuYV viruses. They induced a similar but milder vein clearing phenotype due to lower viral accumulation. This indicates that P0 does not hinder the performances of the TuYV silencing effect and confirms that in the viral infection context, P0 has no major impact on the production, propagation and action of the short distance silencing signal in phloem cells. Finally, we showed that TuYV can be used to strongly silence the phloem specific RTM1 gene. The TuYV-derived VIGS vectors therefore represent powerful tools to easily detect and monitor TuYV in infected plants and conduct functional analysis of phloem-restricted genes. Moreover this example indicates the potential of poleroviruses for use in functional genomic studies of agronomic plants.